IMPLEMENTASI PERLINDUNGAN ANAK BERBASIS PESANTREN PERSPEKTIF MAQASHID AS-SYARI’AH - Taufiqul Mustofa, Muhammad; Al Amin, Habibi (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
Rules related to child protection have been made in such a way, but in reality there are still many acts of discrimination or violence that occur in the educational environment, including in Islamic boarding schools. Islamic boarding schools in carrying out child protection and the inhibiting factors. The results of this study indicate that in relation to the implementation of Islamic boarding school-based child protection, the program is implemented in stages in the religious, educational, social and economic fields. Apart from that, there are still a number of obstacles including the existence of individual boarding school administrators who still do not understand the limits of disciplinary action against students, the existence of several parents of students who do not know/do not understand Islamic boarding school norms and the existence of a hyperprotective attitude from some parents of unscrupulous students. "forced/forced" to seek knowledge at the Islamic boarding school (wrong intention) so that it encourages students to violate the rules of Islamic boarding schools.